THE RELATIONSHIP BETWEEN SUBJECTIVE NORMS WITH HOUSEWIFE’S INTENTION TO ACT ON OF WASTE ISSUES IN CIDEPIT RIVER, SUB-DISTRICT OF SEMPLAK, CITY OF BOGOR - Septi Mulyanti Siregar; Nadiroh Nadiroh; Samadi Samadi (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2019)
Disposing of litter into the river has become a habit for people living around the banks of rivers, rivers, rivers, rivers, and so on. The purpose of this study is to determine the relationship between prevailing norms and spending on littering housewives around the banks of the Cidepit river. This research was conducted in the area of RW 07, Semplak Village, Bogor City in May-June 2018 with a survey method using quantitative. The numbers of samples in this study were 116 people, variables consisting of, and intentions of garbage, and types of data. The second variable is primary data obtained through questionnaires by respondents. Based on the results obtained Pearson r value of 0.319 with Sig. (2-tailed) equal to 0,000 or less than 0.05 Is there a positive relationship between subjective norms (subjective norms) and intentions of intentions in housewives around the banks of Cidepit River, RW 07, Semplak Village, Bogor city.